PERBANDINGAN AGILITY LADDER EXERCISE METODE LATERAL RUN DENGAN CIRCUIT TRAINING DALAM MENINGKATKAN KELINCAHAN PEMAIN FUTSAL PADA TIM GRIYA TANSA TRISNA DALUNG - Gede Denny Wiradarma; Anak Ayu Nyoman Trisna Narta Dewi; I Gusti Ayu Artini (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2018)
Agility is a form of exercise with fast movement and changing direction and agile. Seeing the many agility exercises targeting the coordination of muscle nerves, reaction speed, balance, muscle strength alone but did not increase flexibility significantly. This study aims to determine the comparison of agility ladder exercise lateral run method with circuit training in terms of increased agility. The research design with experimental Pre-Test and Post- Test Two Group Design, sample of 18 people divided into 2 groups with simple random sampling. The sample of this research is futsal team player Griya Tansa Trisna Dalung. Group 1 was given Agility Ladder Exercise Lateral Run method and group 2 was given Circuit Training, research for 5 weeks with dose of exercise 3 times in one week. Illinois Agility run test used before and after training to measure agility. Normality test using Saphiro Wilk, homogeneity using Levene's test and hypothesis testing using Independent T-test. The data mean group 1 and group 2 were normal and homogeneous distributed with mean increase in group 1 was 2.89 and group 2 was 4.47. Difference between group 1 and group 2 was obtained p = 0,000 (p <0,05) meaning statistically significant difference.This research concludes circuit training exercises more effective are used to improve agility on the team's futsal player Griya Tansa Trisna Dalung. Keywords: agility, agility ladder exercise, lateral run method, circuit training